Rozwiązania Osobliwe Płyt Wzmocnionych Zebrami Jednostronnymi - Ganowicz, R. (Engineering Transactions, 1961)
The problem solved is that of the infinite plate stiffened with ribs on one side and loaded with a concentrated force. This solution corresponds to the singular solutions for isotropic, [1],and anisotropic plates, [2], [3], known from the literature and enabling us to determine the influence surfaces of plates with any contour and any support conditions. The singular solutions discussed in the present paper concern plates satisfying PFLÜGER’S conditions, [5], and have been obtained by making use of the author’s results for the simply supported strip, [4]. All the mechanical quantities are obtained in the form of closed expressions. As an illustration a numerical example is given, where a singular solution is found for the bending moment.